1999
DOI: 10.1523/jneurosci.19-10-03818.1999
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Stimulates cGMP Production and Mimics Synaptic Responses in Metacerebral Neurons ofAplysia

Abstract: Nitric oxide (NO) acts as a neurotransmitter and neuromodulator in the nervous systems of many vertebrates and invertebrates. We investigated the mechanism of NO action at an identified synapse between a mechanoafferent neuron, C2, and the serotonergic metacerebral cell (MCC) in the cerebral ganglion of the mollusc Aplysia californica. Stimulation of C2 produces a decreasing conductance, very slow EPSP in the MCC. C2 is thought to use histamine and NO as cotransmitters at this synapse, because both agents mimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 35 publications
3
56
0
Order By: Relevance
“…At the cellular level, it has been demonstrated that NO can act as the sole anterograde messenger between two identified Lymnaea feeding motoneurons (Park et al 1998) or as a co-transmitter at the synapse between the cerebral C2 neuron and the metacerebral giant cell (MGC) in Aplysia, which is homologous to the Lymnaea CGC (Jacklet 1995;Koh and Jacklet 1999). In Aplysia, NO enhances the excitability of the MGC, which potentially enhances the influence of the MGCs on feeding activity (Jacklet and Tieman 2004).…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, it has been demonstrated that NO can act as the sole anterograde messenger between two identified Lymnaea feeding motoneurons (Park et al 1998) or as a co-transmitter at the synapse between the cerebral C2 neuron and the metacerebral giant cell (MGC) in Aplysia, which is homologous to the Lymnaea CGC (Jacklet 1995;Koh and Jacklet 1999). In Aplysia, NO enhances the excitability of the MGC, which potentially enhances the influence of the MGCs on feeding activity (Jacklet and Tieman 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, regulation of NR1 by protein kinases can influence synaptic transmission and plasticity or lead to molecular and functional heterogeneity of the NMDA receptor family in Aplysia and Lymnaea. The putative cGMPdependent regulatory sites in the NR1s found in MCC neurons may be involved in mediating NO signaling (e.g., from NOS containing C2 neurons [Jacklet, 1995;Koh and Jacklet, 1999;Moroz, 2006]). Nitric oxide and cGMP are also known to control NR1/NMDA channel activity (Jurado et al, 2003;Stanton et al, 2003).…”
Section: Nmda Receptors In Molluscs and Their Relevance To Memory Mecmentioning
confidence: 99%
“…A suction electrode was attached to one of the cerebral-buccal connectives (CBCs). Recordings from the CBC allowed us to monitor the activity of the MCC, a giant neuron that is excited via the release of both NO and histamine (McCaman and Weinreich 1985;Koh and Jacklet 1999). After replacing the medium with ASW, MCC activity was induced via the nonhydrolyzable cholinergic agonist carbamyl-choline (Carbachol, or CCh; 2 3 10 À4 M), which was applied for 5 min (Susswein et al 1996;Katzoff et al 2006).…”
Section: Acute MCC Activitymentioning
confidence: 99%